Detecting subclinical cardiotoxicity during immune checkpoint inhibitor therapy: a combined GLS and ECG repolarization analysis - Oksen, Dogac; Gecit, Muhammed Heja; Arslan, Sukru; Aslan, Muzaffer; Yavuz, Yunus Emre; Secmeler, Saban; Oktay, Veysel (Frontiers in Oncology, 2025)
PurposeImmune checkpoint inhibitors (ICIs) can induce subclinical cardiac dysfunction that often goes undetected by conventional monitoring. This study evaluated whether echocardiographic global longitudinal strain (GLS) and electrocardiographic (ECG) repolarization parameters could detect early, subclinical cardiotoxicity in patients with cancer and without pre-existing cardiovascular disease undergoing ICI therapy.MethodsA observational cohort study included 74 patients with cancer treated with ICIs between January 2023 and August 2024. Echocardiographic GLS measurements and detailed ECG analyses were performed at baseline and repeated at 6 months. Cardiotoxicity was defined as a significant reduction in GLS or left ventricular ejection fraction. Correlations between GLS and ECG repolarization parameters were statistically assessed.ResultsAt 6 months, significant subclinical myocardial impairment was observed, with GLS decreasing from 19.40 ± 1.07% to 17.70 ± 1.62% (p<0.001). Notable ECG changes included increased QT dispersion (40.10 ± 10.55 ms to 50.20 ± 15.30 ms, p=0.001), QTc prolongation (420.45 ± 20.60 ms to 430.75 ± 25.40 ms, p=0.013), increased Tp-e interval (80.21 ± 10.45 ms to 85.30 ± 12.40 ms, p=0.021), and elevated heart rate (72.21 ± 8.40 bpm to 75.35 ± 9.15 bpm, p=0.037). GLS was negatively correlated with QT dispersion (r = -0.845, p < 0.05) and Tp-e intervals (r = -0.478, p = 0.052).ConclusionGLS and ECG repolarization parameters, particularly QT dispersion and Tp-e intervals, effectively detect subclinical myocardial dysfunction in patients with cancer undergoing ICI therapy. These findings underscore the importance of comprehensive cardiac monitoring to enable early intervention and mitigate cardiotoxicity risk during immunotherapy.